Do stereotypes matter for brand attachment?. Issue 4 (4th December 2020) - Japutra, Arnold; Molinillo, Sebastian; Ekinci, Yuksel
Abstract : Purpose: This study aims to investigate the role of destination brand stereotypes in predicting destination brand attachment (DBA). Design/methodology/approach: Using survey data from 612 Indonesian respondents, the conceptual framework is tested by applying structural equation modeling analysis. Findings: The results show that the four components of destination branding contribute to DBA through brand stereotypes. Originality/value: Based on the stereotype content model, this study explores how two cognitive (i.e. brand awareness and perceived quality) and two affective (i.e. ideal self-congruence and enduring culture involvement) components build destination brand stereotypes, which in turn increase DBA.